Studies Towards The Synthesis of Tartrolons D and E - Sunnapu, Ranganayakulu; Rehman, Mintu; Nanoth, Sreya; Rajendar, Goreti (Synthesis, 2023)
A concise and stereoselective synthesis of a key fragment C3-C22 unit of tartrolons D and E is demonstrated. Three crucial fragments are combined to form the 20-carbon chain, which contains four stereogenic centers in the monomeric unit of both natural products. The crucial fragments were synthesized in highly enantioselective routes from commercial starting compounds in two, eight, and two steps, respectively, and coupled using palladium-catalyzed Sonogashira coupling and directed 1,5-asymmetric aldol reaction as key steps.
Keywords: macrodiolides; tartrolons; C3-C22 fragment; 1,5-asymmetric aldol; Sonogashira coupling